Anomalous origin of the left circumflex coronary artery: A case report - Dursunoğlu, Dursun (Pulsus Group Inc, 2007)
The anomalous origin of the left circumflex coronary artery from the right sinus of Valsalva is a relatively common anatomical variation. Difficulties may occur in the diagnostic procedure, but recognition and adequate visualization of the anomaly is essential for proper patient management, especially in patients undergoing evaluation for percutaneous coronary intervention, coronary artery surgery or prosthetic valve replacement. In the present report, a patient who had undergone percutaneous coronary intervention for a right coronary artery lesion after inferior myocardial infarction is described. The anomalous origin of the left circumflex coronary artery arising independently from the right sinus of Valsalva was previously undetected.